Investigating the effect of learning method and motivation on learning performance in a business simulation system context: An experimental study. (December 2018) - Lin, Hsin-Hui; Yen, Wan-Chu; Wang, Yi-Shun
Abstract: With the proliferation of business simulation systems used in business education, an understanding of the factors of a simulation-based learning environment that contribute to learning performance within instructional settings is essential. This study aims to explore the effect of learning method (individual mode vs. collaborative mode) and learning motivation (low vs. high) on learning performance in a simulation-based business learning context by conducting an experiment with a 2 × 2 factorial design. Virtual Business Retailing (VBR) software, a business simulation system for convenience store operation, is adopted to build a retailer simulation-based learning environment. Our results reveal that the difference in students' learning performance between individual mode and collaborative mode is significant. However, learning motivation does not have a significant impact on learning performance. Further, learning motivation is an important moderator for the effect of learning method on learning performance. These findings provide several important theoretical and practical implications for the educational use of business simulation systems. Highlights: We explore the effect of learning method and learning motivation on learning performance in a business simulation context. The difference in students' learning performance between individual mode and collaborative mode is significant. Learning motivation is an important moderator for the effect of learning method on learning performance. The findings provide important theoretical and practical implications for educational use of business simulation systems.